Enhanced thrombolysis by endovascular low-frequency ultrasound with bifunctional microbubbles in venous thrombosis: in vitro and in vivo study - Wang, Zhaojian; Pan, Yunfan; Huang, Huaigu; Zhang, Yuan; Li, Yan; Zou, Chenghong; Huang, Guanghua; Chen, Yuexin; Li, Yongjian; Li, Jiang; Chen, Haosheng (Frontiers in Bioengineering and Biotechnology, 2022)
There is a need to improve the efficacy and safety of endovascular techniques in venous thrombotic diseases, and microbubble enhanced sonothrombolysis is a promising approach. However, whether endovascular low-frequency ultrasound (LFUS) can be utilized in microbubble enhanced sonothrombolysis is unclear. Here, we present a catheter-based thrombolytic system that combines unfocused low-frequency low-intensity ultrasound with novel fibrin-targeted drug-loaded bifunctional microbubbles. We develop an in vitro flow model and an in vivo rabbit inferior vena cava (IVC) thrombosis model to evaluate the safety and efficacy of the thrombolytic system. The results indicate that microbubble enhanced sonothrombolysis with endovascular LFUS treatment for 30 minutes is equally effective compared to pure pharmacologic treatment. Furthermore, the thrombolytic efficacy of this system is safely and substantially improved by the introduction of a fibrin-targeted drug-loaded bifunctional microbubble with a reduction of the fibrinolytic agent dosage by 60%. The microbubble enhanced endovascular LFUS sonothrombolysis system with excellent thrombolytic efficacy may serve as a new therapeutic approach for venous thrombotic diseases.